New and rarely found species of asynaptine Porricondylinae (Diptera: Cecidomyiidae) in northern Europe - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2019)
An ongoing taxonomic inventory of mycophagous gall midges (Cecidomyiidae) in Sweden has revealed several previously unnamed species of asynaptine Porricondylinae, which are described here on the basis of male adults mostly from Malaise trap catches. The new species are classified and named as follows: Asynapta inflatoides sp. nov., A. rickebasta sp. nov., A. taigensis sp. nov., Camptomyia capitata sp. nov., C. hedmarki sp. nov., C. oldhammeri sp. nov., C. rhynchostylata sp. nov., and Stackelbergiella sikorai sp. nov. Specimens studied here prove the presence of both Asynapta inflatoides and A. taigensis in Finland, and of Stackelbergiella sikorai in Estonia. Other species new to the Finnish fauna are Asynapta thuraui Rübsaamen and Camptomyia ulmicola Mamaev, whereas Asynapta inflata Spungis has to be deleted from the Finnish checklist. Males of two species recorded in Sweden for the first time, and three species whose Swedish distribution is reconfirmed here, are redescribed: Asynapta baltica Spungis; A. inflata; Camptomyia fulva Mamaev; C. piptopori Panelius; and C. ulmicola. New junior synonyms recognized here are Niladmirara Fedotova syn. nov. (of Camptomyia Kieffer) and Asynapta panzari Jaschhof & Jaschhof syn. nov. (of A. breviata Spungis). The genitalic morphology of male Asynaptini is reinterpreted to include two pairs of parameres in the ancestral ground pattern. The extraordinary diversity of male genitalic structures found in asynaptine genera is highlighted, along with considerations of how this source of information can be exploited for the benefit of classification. Small-area remnants of ancient, naturally grown forest are shown to support populations of previously unnamed species of Asynaptini.